2015
DOI: 10.1177/0284185115608658
|View full text |Cite
|
Sign up to set email alerts
|

CT and MRI imaging features and long-term follow-up of adult Wilms’ tumor

Abstract: Adult WT tends to be a large tumor, isointense or hypointense on T2W imaging with enhancement less than normal renal parenchyma in all phases. The long-term follow-up results demonstrated the poor prognosis of the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Conversely, it is very rare in adults, with an incidence rate of less than 0.2 per million per year 2. The imaging characteristics in our patient are congruent with those described in the literature for adult Wilms’ tumour 3. Histology is required for definitive diagnosis.…”
Section: Descriptionsupporting
confidence: 83%
“…Conversely, it is very rare in adults, with an incidence rate of less than 0.2 per million per year 2. The imaging characteristics in our patient are congruent with those described in the literature for adult Wilms’ tumour 3. Histology is required for definitive diagnosis.…”
Section: Descriptionsupporting
confidence: 83%
“…). They also reported that Wilms’ tumors have a cystic component and hemorrhage in their images; this was not evident, perhaps because of the small size of the tumor. Diagnosis was difficult to define because the tumor did not have specific characteristics due to its small size.…”
Section: Discussionmentioning
confidence: 95%
“…Wu et al . reported the image findings of 16 cases of adult nephroblastoma . On dynamic CT, the CT values for Wilms’ tumor were lower than that of the renal cortex and medulla on early and delayed phase.…”
Section: Discussionmentioning
confidence: 99%
“…Although about 95% of Wilms tumor may be predicted with imaging (ultrasound, computed tomography -CT, and magnetic resonance imaging -MRI), however in adults, CT or MRI may aid in diagnosis. 1,7 Immunohistochemistry may prove useful in the diagnosis of Wilms tumor, with positivity for cytokeratin, NSE, and vimentin. 6 There is no standard therapy for treating patients with adult Wilms tumor.…”
Section: Discussionmentioning
confidence: 99%